Solid-Phase Synthesis of Head to Side-Chain Tyr-Cyclodepsipeptides Through a Cyclative Cleavage From Fmoc-MeDbz/MeNbz-resins - Acosta, Gerardo A.; Murray, Laura; Royo, Miriam; de la Torre, Beatriz G.; Albericio, Fernando (Frontiers in Chemistry, 2020)
Cyclic depsipeptides constitute a fascinating class of natural products. Most of them are characterized by an ester formed between the β-hydroxy function of Ser/Thr -and related amino acids- and the carboxylic group of the C-terminal amino acid. Less frequent are those where the thiol of Cys is involved rendering a thioester (cyclo thiodepsipeptides) and even less common are the cyclo depsipeptides with a phenyl ester coming from the side-chain of Tyr. Herein, the preparation of the later through a cyclative cleavage using the Fmoc-MeDbz/MeNbz-resin is described. This resin has previously reported for the synthesis of cyclo thiodepsipeptides and homodetic peptides. The use of that resin for the preparation of all these peptides is also summarized.